Keterampilan Khithabah untuk Meningkatkan Maharah Kalam di Pondok Pesantren Darul Amin Bustanul Arifin - Ritonga, Nur'ainun; Gamasari, Rita; Rosada, Bintang; Ismil Hakim, Rani; Daulay, Irmasani (Universitas Islam Negeri Sumatera Utara, 2023)
Islamic Boarding School of Darul Amin Bustanul Arifin is one of the Islamic boarding schools located in the Mandailing Natal regency. Based on preliminary research in the field by interviewing the students, the Arabic speaking skill of the students at the Islamic Boarding School of Darul Amin Bustanul Arifin was considered as low. In consequence, the team of community service consisting of Arabic language and literature lecturers was motivated to organize a relevant program on Arabic language enhancement through training in speech or khithabah. This training was hoped to give an improvement on students’ Arabic speaking skills. In addition, this program was expected to trigger the students to be self-confident to deliver a speech in front of the audience, particularly when expressing ideas, sharing new knowledge, and preaching religious messages to society. This program applied two methods namely the speech method delivered by the team of community service consisting of Arabic language and literature lecturers and the communicative method through question-answer sessions related to the program’s materials which were strengthened by displaying the speech text and allowing students to practice the speech by turns. The program of community service conducted by the team of Arabic Language and literature lecturers at the Islamic boarding school of Darul Amin Bustanul Arifin run very well. The result of the program is expected to give benefit students’ Arabic speaking skills pertinently improving their self-confidence for speech delivery in front of the audience.Keywords: training of speech, Speaking Skills, Islamic boarding school, Darul Amin Bustanul Arifin.